Characterizing Breast Tissue Samples with Integrated Imaging - Douplik, Alexandre; Moradi, Shahram; D'Ippolito, Alexander; Dingle, Kate; Michel, Marius; Easson, Alexandra (Latin America Optics and Photonics Conference, LAOP 2024 in Proceedings Optica Latin America Optics and Photonics Conference, LAOP 2024, 2024)
A method was developed to distinguish cancerous from non-cancerous breast tissue using white and UV light imaging, analyzing fluorescence intensity. Pathologist-marked images confirmed accuracy, optimizing tissue thickness for transmission mode analysis.
CRIS-Team Scopus Importer:2025-04-01